Activisme politique et gouvernance au Niger : nature et formes de la répression numérique - Gado ALZOUMA (Tic & Société)
Although digital activism has strengthened in recent years on the African continent with the expansion of mobile phones and social networks, dictatorial or authoritarian governments have adapted their methods of repression to the new situation. This can be seen in particular in how these governments use ICTs to consolidate their power and/or exercise greater surveillance and stronger repression on citizens. In this article, we explore the case of Niger to highlight the multiple forms of repression implemented by African authoritarian regimes in response to attempts to use ICTs to expand the space of public liberties. We demonstrate that in authoritarian states characterized by technological deprivation, in particular limited access to digital technologies, low levels of education and a low sophistication of the state apparatus, digital repression is distinguishable from traditional forms of repression only in that it exclusively targets users of the Internet and social networks.